A rare, potentially life‐threatening presentation of passenger lymphocyte syndrome. Issue 5 (28th March 2017) - Gniadek, Thomas J.; McGonigle, Andrea M.; Shirey, R. Sue; Brunker, Patricia A.; Streiff, Michael; Philosophe, Benjamin; Bloch, Evan M.; Ness, Paul M.; King, Karen E.
Abstract : BACKGROUND: Passenger lymphocyte syndrome occurs when donor lymphocytes are transplanted with a solid organ and produce alloantibodies that react with antigens on the recipient's red blood cells (RBCs). Typically, passenger lymphocyte syndrome presents as immunoglobulin G antibody‐mediated, extravascular hemolytic anemia with reticulocytosis. Often, the donor was alloimmunized before transplantation. CASE REPORT: A 34‐year‐old Group O, D+ man with a negative antibody screen received a liver transplant from a Group O, D− donor. Twenty Group O, D+ RBC units were transfused on Postoperative Days (PODs) 0 through 2. On POD 7, the patient developed anemia, a weakly positive antibody screen, and a positive direct antiglobulin test with anti‐D in the eluate. After POD 8, a D− transfusion protocol was initiated. Despite laboratory evidence of hemolysis, two initial peripheral blood smears showed no increase in schistocytes or spherocytes, the reticulocyte count was depressed, and a marrow biopsy revealed erythroid hyperplasia. Eventually, anemia resolved after a period of medication non‐compliance; however, a positive direct antiglobulin test persisted to the last follow‐up date (POD 233). RESULTS: Other potential causes of aplastic anemia were investigated, but no alternative cause was found. History excluded passive anti‐D. D+, LW− cells were reactive, excluding anti‐LW. Genotyping showed no evidence of a partial D genotype. Chart review revealed that the liver donor had a history of anti‐D. A diagnosis of passenger lymphocyte syndrome was reached. CONCLUSION: Although antibody‐mediated hemolytic anemia has been reported to cause reticulocytopenia in the presence of marrow erythroid hyperplasia, this report of passenger lymphocyte syndrome causing a similar post‐transplant anemia in association with reticulocytopenia is noteworthy.